David and Goliath - Du Bouetiez, Anne-Sophie; Furlaud, Sophie; Hata, Koshiro ([Quezon City] Adarna House, 2011)
Retells the Bible story of the shepherd boy who saved his people by killing a giant.
This story is about how a young shepherd boy won a fight against a big, strong man and became the great king of Israel.
"Originally published in Bayard Jeunesse/Pomme d'api Soleil (2007-2009)."
Published jointly with Bayard Assumption Media Foundation.
Keywords: David -- King of Israel -- Juvenile literature; Goliath -- (Biblical giant) -- Juvenile literature; David -- King of Israel; Goliath -- (Biblical giant).; Bible stories -- O.T.